Hybrid U-shaped-microbend SMF evanescent wave sensor for river water quality assessment: a preliminary study / Amirul Hazim Kamarulzaman and Wan Maisarah Mukhtar - Kamarulzaman, Amirul Hazim; Mukhtar, Wan Maisarah (Faculty of Applied Sciences, 2020)
A hybrid U-shaped-microbend fiber optic evanescent wave sensor was developed by combining two types of bending structures on the optical communication single mode optical fiber (SMF28). To study the effect optical microbending on the output power, corrugated plates consisted of cylindrical structured surface with various distance between the glass rods of 6 cm, 12 cm and 18 cm were constructed. The macrobending effect was introduced by bending the SMF into two shapes, namely U-shaped and Sshaped. The bare SMF with various bending designs were immersed into numerous water sources from Sg. Simin, Sg. Batang Benar and Sg. Klang. The output demonstrated that Sg. Simin was the most polluted river, followed by Sg. Klang and Sg. Batang Benar using U-shaped microbend SMF with distance between glass rod of 6cm and 1310 nm laser source. This result showed an excellent agreement with water quality index (WQI) data released by the Department of Environment (DOE), Malaysia. Maximum optical output power was obtained by using Sg. Simin’s water sample due to better light absorption from the evanescent waves by the pollutant particles, that avoided light leakage in comparison with less polluted water sources. The optimum sensing performance was successfully resulted by using U-shaped SMF due to its durability and uniform evanescent waves radiated from the cladding. In conclusion, the hybrid U-shaped-microbend SMF sensor based on evanescent waves propagation portrays an excellent potential to detect water pollution by monitoring the presence of pollutants around the fiber.